Occupational safety and health hazards associated with the slaughtering and meat processing industry in urban areas of Zimbabwe: A case study of the Gweru city Municipal Abattoir - Steven Jerie; Kennedy Matunhira (Department of Geography and Resource Development, University of Ghana., 2023)
Abstract